Water absorption properties of kenaf fibre-poly(vinyl alcohol) composites - Tan, B.K.; Ching, Yern Chee; Gan, Seng Neon; Ramesh, Singh; Rahman, M.R. (Taylor & Francis, 2014)
The composite was prepared by mixing aqueous solution of different ratios of poly(vinyl alcohol) into dried kenaf fibres. The water absorbency of this polymer composite was investigated. It was found that the polymer composite starts to swell when immersed into water and reaches the highest water absorption percentage in the first 1 hour. The highest water absorption percentage was 273 and 251% for the composite with 2 and 10 wt% of poly(vinyl alcohol), respectively, in 24 hours. The high water absorbency could be due to the interaction of water with the hydroxyl group in the poly(vinyl alcohol) and fibres, similar to other reported works on cellulose composites. Interestingly, the poly(vinyl alcohol) in the composite only starts to dissolve very slowly over more than 7 days before the kenaf fibres started to dropout from the composite. This water absorption capability of the polymer composite could have potential applications that require high water-retaining properties. Besides, this composite is non-toxic.